Comparative effectiveness of diabetes self-management education and support intervention strategies among adults with type 2 diabetes in Texas - Ory, Marcia G.; Han, Gang; Nsobundu, Chinelo; Carpenter, Keri; Towne, Samuel D.; Smith, Matthew Lee (Frontiers in Public Health, 2025)
BackgroundWith approximately 1-in-10 Texas estimated to be living with Type 2 Diabetes Mellitus (T2DM), and the steadily rising healthcare costs associated with non-managed T2DM, efforts are needed to help patients manage their diabetes and avoid costly health consequences. While many diabetes self-management interventions and solutions exist to improve health among people living with T2DM, less is known about the relative effectiveness of these interventions based on their delivery format and when used in combination. The purpose of this study was to identify the effectiveness of three intervention modalities to reduce hemoglobin A1c (A1c) among Texans with T2DM living in rural and urban settings.MethodsA three-arm randomized controlled trial (RCT) was conducted from November 2020 through March 2022. The three modalities included: (1) asynchronous virtual education and support program with one-on-one follow-up counseling [i.e., virtual Making Moves with Diabetes (vMMWD)]; (2) technology-based education and support (i.e., TBES); and (3) combined modality where participants sequentially received vMMWD and TBES (i.e., combined). Data were collected at baseline and again at 3- and 6-month follow-up. Using an intent-to-treat analysis, constrained longitudinal data analysis models were fitted to identify and compare changes in A1c over time.ResultsFindings demonstrate the positive effects of all three intervention modalities (i.e., vMMWD, TBES, and combined) to significantly reduce A1c among participants. Longitudinal analyses identified that initial reductions in A1c at 3-month follow-up were sustained at 6-month follow-up. Findings were consistent among rural- and urban-residing participants.ConclusionThis RCT highlights the universal benefits of self-paced virtual diabetes self-management interventions to reduce A1c among Texans with unmanaged T2DM. Such low-cost interventions may be widely applicable for different settings and populations.